Transformation of QRIS-Based Urban MSME Payment Methods - Yuwana, Haris Eka; Xavier, Murphy; Elliot, McCarty; Oscar, Scherschligt (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The rise of social media as a means of interaction with others and building networks is a characteristic of the era modern. Purpose. To find out payments using the Qris Method. Review literature. Sources for this research were obtained from journal articles, books, and other documentation that explained theory and knowledge. Results. The contents of this activity try to explain as much as possible the guaranteed security of QRIS and the good way to use it so as not to get involved in cybercrime. Conclusion. UMKM is becoming more aware of payments using A pinch